Energy and Exergy Analysis of Different Exhaust Waste Heat Recovery Systems for Natural Gas Engine Based on ORC (2019)
Waste heat recovery (WHR) from exhaust gases in natural gas engines improves the overall conversion efficiency. The organic Rankine cycle (ORC) has emerged as a promising technology to convert medium and low-grade waste heat into mechanical power and electricity. This paper presents the energy and exergy analyses of three ORC–WHR configurations that use a coupling thermal oil circuit. A simple ORC (SORC), an ORC with a recuperator (RORC), and an ORC with double-pressure (DORC) configuration are considered; cyclohexane, toluene, and acetone are simulated as ORC working fluids. Energy and exergy thermodynamic balances are employed to evaluate each configuration performance, while the available exhaust thermal energy variation under different engine loads is determined through an experimentally validated mathematical model. In addition, the effect of evaporating pressure on the net power output, thermal efficiency increase, specific fuel consumption, overall energy conversion efficiency, and exergy destruction is also investigated. The comparative analysis of natural gas engine performance indicators integrated with ORC configurations present evidence that RORC with toluene improves the operational performance by achieving a net power output of 146.25 kW, an overall conversion efficiency of 11.58%, an ORC thermal efficiency of 28.4%, and a specific fuel consumption reduction of 7.67% at a 1482 rpm engine speed, a 120.2 L/min natural gas flow, 1.784 lambda, and 1758.77 kW of mechanical engine power